Overview and characterization of penile cancer content across social media platforms - Ortiz-Guerra, Ruben Alejandro; Jaime-Casas, Salvador; Martinez-Cannon, Bertha Alejandra; Ariza-Avila, Jose C.; González-Morales, Ana P.; Bardan-Duarte, Andrea; Remolina-Bonilla, Yuly A.; Spiess, Philippe E.; Bourlon, Maria T. (Frontiers in Oncology, 2023)
BACKGROUND: Social media platforms (SMP) are an emerging resource that allows physicians, patients, and families to converse on cancer prevention, diagnosis, and treatment. We aimed to characterize penile cancer (PC) content shared on SMP. METHODS: We searched PC posts on Twitter, Facebook, and Instagram from July 1st, 2021, through June 30th, 2022. Two independent, blinded reviewers analyzed the hashtags: #PenileCancer, #PenileCancerAwareness, and #PenileNeoplasm. Descriptive statistics were used for posts characterization, Pearson´s correlation coefficient for associations, and Cohen's weighted kappa coefficient for inter-rater agreement rate. RESULTS: A total of 791 posts were analyzed, with Twitter accounting for 52%, Facebook for 12.2%, and Instagram for 35.5%, and. Most posts originated from high-income countries, such as the United Kingdom (48.8%). We found no correlation between the number of posts with PC incidence (p = 0.64) or users on SMP (p = 0.27). Most accounts were classified as "support and awareness communities" (43.6%) and "physicians and clinical researchers" (38.2%). Urology was the most common medical specialty to post (60.9%), followed by oncology (11.3%). Most posts were classified as “prevention and awareness for users” (45.1%). Global inter-reviewer agreement rate was almost perfect (k=0.95; p≤0.01). On Twitter, “physicians and clinical researchers” shared more content on "treatment updates and medical papers published in medical journals,” while on Facebook and Instagram, “support and awareness communities” focused on "personal and support comments.” CONCLUSIONS: Overall, the number of PC posts was low compared to other neoplasms across the SMP evaluated in this study. “Physicians and clinical researchers” shared more content on Twitter, while “support and awareness communities” on Facebook and Instagram. Encouraging the use of a common SMP among the medical community and general users could lead to a more effective communication between physicians, patients, and support groups, and to increased awareness of PC.